2023
DOI: 10.3390/nu15092199
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of Inflammatory Pathways and Their Relationship with Anti-Hypothalamic Autoantibodies in Patients with Anorexia Nervosa

Abstract: Background: Despite several attempts, the etiopathogenesis of anorexia nervosa (AN) is still unknown. However, the activation of the immune response in neuropsychiatric diseases, including AN, is increasingly evident. We aimed to explore immune response parameters in patients with AN and identify the link between the presence of specific autoantibodies for hypothalamic antigens and the inflammatory response. The relationship between inflammatory markers and the duration of the disease has been also investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Several blood alterations, including leukopenia, polycythemia, and thrombocytopenia, have also been found in young male patients with AN [ 14 ]. Furthermore, elevated proinflammatory cytokines, with increased levels of tumor necrosis factor (TNF)-α, interleukin (IL)-1α, and IL-6 [ 15 , 16 ], phenotypes associated with modulation of the cellular components of the adaptive and innate immune system, have been reported in patients with AN [ 11 ]. Therefore, the significant role of cytokines in the modulation of inflammation, control of infections, regulation of neurotransmitter systems, neuroplasticity, and neuroendocrine functioning is recognized [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several blood alterations, including leukopenia, polycythemia, and thrombocytopenia, have also been found in young male patients with AN [ 14 ]. Furthermore, elevated proinflammatory cytokines, with increased levels of tumor necrosis factor (TNF)-α, interleukin (IL)-1α, and IL-6 [ 15 , 16 ], phenotypes associated with modulation of the cellular components of the adaptive and innate immune system, have been reported in patients with AN [ 11 ]. Therefore, the significant role of cytokines in the modulation of inflammation, control of infections, regulation of neurotransmitter systems, neuroplasticity, and neuroendocrine functioning is recognized [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the significant role of cytokines in the modulation of inflammation, control of infections, regulation of neurotransmitter systems, neuroplasticity, and neuroendocrine functioning is recognized [11]. Thus, the observation that inflammation varies with the duration of the disease seems to validate the hypothesis that the role of the immune system can actually be causal in the pathogenesis and maintenance of AN [16]. It has been suggested that autoimmunity may be one of the pathogenetic causes of AN.…”
Section: Introductionmentioning
confidence: 99%